RESPIRATORY TRACT BURN AS A FACTOR IN THE SEVERITY OF BURN DISEASE: DIAGNOSIS, PATHOGENESIS AND CLINICAL COURSE - A.U, Ziyodullaev; I.B, Mustafakulov; Z.A, Juraeva (Research Focus International Scientific Journal, 2026)
Respiratory tract burns are one of the most significant factors determining the severity and outcome of burn disease. This study presents an analysis of clinical, functional, and morphological changes in the respiratory system in 144 patients with respiratory tract damage secondary to burn injury. The pathogenesis, clinical course, and diagnostic capabilities of modern research methods are examined. Respiratory tract damage is associated with significant ventilation and gas exchange impairment, a high risk of infectious complications, and a significant increase in mortality. Comprehensive diagnostics using endoscopic and cytological methods enable timely detection of the extent of damage and prognosis of the disease.